IMPROVING THE EFFICIENCY OF COMBINED FRICTION OF SHOCK-ABSORBING DEVICES ON THE BASIS OF THE PMK-110A - Kehlin, B. H.; Boldyriev, O. P.; Ivanov, O. V.; Stupin, D. O. (Science and Transport Progress, 2004)
Questions of the development and application of the combined frictional shock-absorbers of Т1 and Т2 classes which use elastic elements made of Durel polymeric material as the working elements are considered.